2021
DOI: 10.3389/fonc.2021.740484
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Gene-Set Signature in Early-Stage Hepatocellular Carcinoma and Relevant Immune Characteristics

Abstract: BackgroundThe incidence of hepatocellular carcinoma (HCC) is rising worldwide, and there is limited therapeutic efficacy due to tumor microenvironment heterogeneity and difficulty in early-stage screening. This study aimed to develop and validate a gene set-based signature for early-stage HCC (eHCC) patients and further explored specific marker dysregulation mechanisms as well as immune characteristics.MethodsWe performed an integrated bioinformatics analysis of genomic, transcriptomic, and clinical data with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…The generation of tumor is almost caused by inducing certain key lesions in host cells, such as controlling cell proliferation, apoptosis, and differentiation ( 16 ). Therefore, carcinogen is the first choice to induce HCC in mice to mimic the progression in human beings, and the most commonly used inducers include DEN, AFB1, and CCl 4 ( 17 , 18 ). The classification, advancement, and application of various mouse HCC models are shown in Figure 1 .…”
Section: Chemically Induced Mouse Hepatocellular Carcinoma Modelsmentioning
confidence: 99%
“…The generation of tumor is almost caused by inducing certain key lesions in host cells, such as controlling cell proliferation, apoptosis, and differentiation ( 16 ). Therefore, carcinogen is the first choice to induce HCC in mice to mimic the progression in human beings, and the most commonly used inducers include DEN, AFB1, and CCl 4 ( 17 , 18 ). The classification, advancement, and application of various mouse HCC models are shown in Figure 1 .…”
Section: Chemically Induced Mouse Hepatocellular Carcinoma Modelsmentioning
confidence: 99%
“…CD8 + T cells are key players that perform anti-tumor immune functions in the TIME and characteristic markers of good prognosis in HCC. They mediate target cell apoptosis by secreting perforin and granzyme or by expressing Fas ligand (FasL) ( 32 , 33 ). Single-cell RNA sequencing indicated that the effector CD8 + T cells in advanced HCC patients were depleted and weakened in cytotoxicity compared to those in early-stage of HCC, which may lead to impaired anti-tumor function ( 34 ).…”
Section: Regulatory Mechanisms Of Ncrnas In Hccmentioning
confidence: 99%